1999
DOI: 10.1524/ract.1999.87.34.151
|View full text |Cite
|
Sign up to set email alerts
|

The Gas Phase Oxide and Oxyhydroxide Chemistry of Trace Amounts of Rhenium

Abstract: SummaryIn preparation of experiments to investigate the chemical properties of bohrium (Bh, element 107) the behaviour of Re, its lighter homologue in group 7, was studied in different oxidizing chemical systems. The adsorption data of Re oxide and oxyhydroxide Compounds on quartz surfaces were evaluated from results of thermochromatography experiments and confirmed in isothermal gas chromatography experiments applying 1 cm as Standard state for the simple gas adsorption process: An on-line Separation method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 20 publications
0
14
0
1
Order By: Relevance
“…However, test experiments with Re have shown that the oxy hydroxide system has some potential for future studies of Bh, especially if volatile Po, Pb, and Bi contaminations, which mask the a-spectra and limit the sensitivity, can be avoided by using a physical preseparator. [234][235][236] To date, the only information on chemical properties of Bh was obtained in gas chromatographic experiments [99] on the oxy chlorides which were performed by Eichler and coworkers at the PSI Philips cyclotron in Villigen. Extensive tests with Tc and Re tracer activities had been performed previously.…”
Section: Methodsmentioning
confidence: 99%
“…However, test experiments with Re have shown that the oxy hydroxide system has some potential for future studies of Bh, especially if volatile Po, Pb, and Bi contaminations, which mask the a-spectra and limit the sensitivity, can be avoided by using a physical preseparator. [234][235][236] To date, the only information on chemical properties of Bh was obtained in gas chromatographic experiments [99] on the oxy chlorides which were performed by Eichler and coworkers at the PSI Philips cyclotron in Villigen. Extensive tests with Tc and Re tracer activities had been performed previously.…”
Section: Methodsmentioning
confidence: 99%
“…Element 108, hassium, was synthesized for the first time in 1984 using the reaction 58 Fe + 208 Pb. The identification was based on observation of three decay chains, which were assigned to 265 Hs [60].…”
Section: The First Hs Chemistry Experimentsmentioning
confidence: 99%
“…The identification was based on observation of three decay chains, which were assigned to 265 Hs [60]. Only one -decay chain was measured in the irradiation of 207 Pb with 58 Fe. The measured event was assigned to the even-even isotope 264 Hs [61].…”
Section: The First Hs Chemistry Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the following application of this system with the aim to search for new bohrium isotopes in the reaction 254 Es+ 16 0 failed [7], in the opinion of the authors caused either by low cross sections or short half-lives of the desired isotopes. Recent model studies deal with gas chromatographic systems using volatile oxo, hydroxo or oxochloride compounds [8,9].…”
Section: Introductionmentioning
confidence: 99%